2020
DOI: 10.21203/rs.3.rs-41970/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Burnout and Depression Among Psychiatry Residents During COVID-19 Pandemic

Abstract: Very few studies have assessed the impact of an infectious outbreak on burnout among health care workers, especially non-frontline health care workers, such as psychiatrists. The role of psychiatrists and other mental health providers in such instances as a source of psychological support to the public and frontline workers is indispensable and valuable. This study aims to assess the prevalence of burnout and depression, and their correlation, during the COVID-19 pandemic among psychiatry residents in Saudi Ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
0
10
0
1
Order By: Relevance
“…8 The global pandemic due to the novel coronavirus disease (COVID-19) likely exacerbated burnout among VHA BHPs as shown in recent studies of BHP experiences outside VHA. [9][10][11] We sought to identify potentially modifiable work-environment characteristics associated with BHP burnout in VHA, the largest integrated health care system in the United States. 12 With few exceptions, 13,14 prior VHA studies on burnout have focused on other provider types, such as primary care physicians or all clinicians and/or conducted facility-level analyses that could not incorporate individuals' experiences in the workplace.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 The global pandemic due to the novel coronavirus disease (COVID-19) likely exacerbated burnout among VHA BHPs as shown in recent studies of BHP experiences outside VHA. [9][10][11] We sought to identify potentially modifiable work-environment characteristics associated with BHP burnout in VHA, the largest integrated health care system in the United States. 12 With few exceptions, 13,14 prior VHA studies on burnout have focused on other provider types, such as primary care physicians or all clinicians and/or conducted facility-level analyses that could not incorporate individuals' experiences in the workplace.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the number of qualified providers could decrease burnout 8 . The global pandemic due to the novel coronavirus disease (COVID‐19) likely exacerbated burnout among VHA BHPs as shown in recent studies of BHP experiences outside VHA 9–11 …”
Section: Introductionmentioning
confidence: 99%
“…However, other studies have shown that junior residents have had more unsatisfactory outcomes, as well as high levels of depressive, anxiety, stress, and burnout symptoms during the COVID-19 pandemic. 28 , 29 The difference in workload and the ability to handle stressors among junior residents may explain this finding. Senior residents usually have more responsibility and employment opportunities, whereas junior residents may have less experience and knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have pointed out the prevalence of symptoms of burnout and depression during the Covid-19 pandemic among psychiatrists, health-care specialists, and social workers. 75 When Lori appears in her Zoom panel, 'She looks dishevelled, though she's trying not to'. 76 Because of her heavy responsibilities during the pandemic, she fails to abide by her schedule, cancelling her previous appointment with Kim and starting this new session late.…”
Section: Zoom Performance Of Corona Chicken (Part Two)mentioning
confidence: 99%